The OPF Formulation and Solution for Energy Router Incorporated AC&DC Network - Duan, Qing; Guo, Jing; Sheng, Wanxing; Sha, Guanglin; Li, Ke-Jun; Xu, Xiaoxian (Recent Advances in Electrical & Electronic Engineering, 2019)
Background: The energy router based on power electronic technology is the core equipment of energy internet. Energy router can control the voltage of the port and regulate the power injected into the network flexibly. It is of great significance to study how the capability of the energy router can be used to improve characteristics of the power system. Methods: Based on the analysis of energy router, we construct a unified AC-DC power flow model for energy router considering its different control modes. Then, we establish an optimal power flow formulation for the energy router incorporated AC-DC network and propose the multi-objective function to optimize the comprehensive performance of the network. Several cases are observed and analyzed on a modified IEEE-57 system. Results: The result verifies that the optimal power flow formulation can optimize the control values of ports of the energy router and improve the operating state of the power system. The optimal target presented in this paper can improve the characteristics of the grid better than a single optimal target. Conclusion: Energy router will play a vital role in the energy internet based on the power system. The characters of the power system can be improved and the operating costs can be reduced by utilizing the functionality of energy router in regulating power flow.
Keywords: Energy router